Benzodiazepine poisoning in elderly - Perković-Vukčević Nataša (Vojnosanitetski Pregled, 2016)
Background/Aim. Benzodiazepines are among the most frequently ingested drugs in self-poisonings. Elderly may be at greater risk compared with younger individuals due to impaired metabolism and increased sensitivity to benzodiazepines. The aim of this study was to assess toxicity of benzodiazepines in elderly attempted suicide. Methods. A retrospective study of consecutive presentations to hospital after self-poisoning with benzodiazepines was done. Collected data consisted of patient's characteristics (age, gender), benzodiazepine ingested with its blood concentrations at admission, clinical findings including vital signs and Glasgow coma score, routine blood chemistry, complications of poisoning, details of management, length of hospital stay and outcome. According the age, patients are classified as young (15-40-year old), middle aged (41-65-year old) and elderly (older than 65). Results. During a 2-year observational period 387 patients were admitted because of pure benzodiazepine poisoning. The most frequently ingested drug was bromazepam, the second was diazepam. The incidence of coma was significantly higher, and the length of hospital stay significantly longer in elderly. Respiratory failure and aspiration pneumonia occurred more frequently in old age. Also, flumazenil was more frequently required in the group of elderly patients. Conclusion. Massive benzodiazepines overdose in elderly may be associated with a significant morbidity, including deep coma with aspiration pneumonia, respiratory failure, and even death. Flumazenil is indicated more often to reduce CNS depression and prevent complications of prolonged unconsciousness, but supportive treatment and proper airway management of comatose patients is the mainstay of the treatment of acute benzodiazepine poisoning.